Examining product and external factors affecting the satisfaction of smartphone consumers - Faiz, Masnan (2015)
Smartphone is a fast growing product in electronic industry and it has been considered important for most of the people following its diversity of its use. The purpose of this study is to identify factors that affect satisfaction of customer after purchasing the product. The study employs quantitative method by surveying Generation Y among in Northern region of Malaysia with 382 respondents was participated. This study employs the Descriptive analysis, Correlation analysis, and Multiple Regression analysis. The results of this study are supported that product judgment, product feature, social influence, brand image and country of origin are correlate significantly with customer satisfaction. Meanwhile, the most influential element on customer satisfaction is product judgment. A discussion of the result of this study will form the basis recommendation for local producers, academicians and other stakeholders of the smartphone industry in Malaysia.